2022
DOI: 10.1371/journal.pone.0275429
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 associated changes in HIV service delivery over time in Central Africa: Results from facility surveys during the first and second waves of the pandemic

Abstract: Introduction The COVID-19 pandemic has impacted population health around the globe, directly and indirectly. The objective of this study was to document changes in HIV care associated with the COVID-19 pandemic at selected clinics in Central Africa, along with clinic-level strategies for minimizing disruptions in HIV care and treatment for people with HIV (PWH). Methods A 51-item questionnaire on COVID-19 pandemic-associated changes in HIV service delivery was completed by clinicians involved in HIV care at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Among the HIV services most affected by the COVID-19 pandemic along with the number of HIV tests were community programs, such as community support groups, patient tracing activities and outreach activities [ 28 ]. The data from our study showed how re-engagement activities were heavily affected by the pandemic, with a decrease compared to the pre-pandemic period, and even at the beginning of the post-pandemic period, the recall ratio made by community health care workers was still at a lower level than in the pre-pandemic period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the HIV services most affected by the COVID-19 pandemic along with the number of HIV tests were community programs, such as community support groups, patient tracing activities and outreach activities [ 28 ]. The data from our study showed how re-engagement activities were heavily affected by the pandemic, with a decrease compared to the pre-pandemic period, and even at the beginning of the post-pandemic period, the recall ratio made by community health care workers was still at a lower level than in the pre-pandemic period.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no differences in HIV service delivery were found based on the HC being located in a central or peripheral area within an urban setting. This may be due to the fact that HCs located in rural areas were not included in the study, as these areas showed the greatest fragility and difficulties in HIV service delivery as they are also highly reliant on community-based activities [ 28 , 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that few countries have adopted multi-month dispensing of drugs 8 , 13 , 22 , 32 while most of the countries could not, due to a shortage of drugs. Such a buffer to health systems against external shocks is advisable.…”
Section: Discussionmentioning
confidence: 99%
“…For example, teleconsultation or virtual platforms, 9 , 12 , 18 , 22 , 23 , 25 , 26 , 28 , 37 was adopted for the smooth functioning of routine HIV care services. In some countries, home delivery 30 of ART medications, multi-month dispensing of ART, 6 , 8 , 13 , 32 provision of self-testing 14 , 20 , 33 and nutritional support 29 were adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Observed decreases in VL monitoring at 36 months are surprising because the subset of patients enrolling in HIV care after guideline adoption with at least 36 months of follow-up time comprised more patients from high-income countries with greater capacity for VL testing [25]. Additionally, while the COVID-19 pandemic is known to have disrupted HIV-related services in many settings [26,27], most patients in our study (>95%) were in countries adopting universal treatment guidelines in 2016 or earlier, meaning that VL monitoring at 36 months after ART initiation reflected prepandemic VL monitoring practices. In sensitivity analyses that excluded countries where outcomes at 36 months could have coincided with the COVID-19 pandemic findings were consistent with our main analyses.…”
Section: Plos Medicinementioning
confidence: 99%